Corn Waste Grinding and Processing Machine as Cattle Feed in The Border Area of The Republic of Indonesia and The Democratic Republic of Timor-Leste (RI-RDTL) - Kamlasi, Yohana; Bouk, Gomera; Bere, Edelnia Kristina; Sinabang, Maria Kristina; Citrawati, Gusti Ayu Oka (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Corn straws and cobs are wastes from corn farming that are not utilized. This corn waste has potential as an alternative use for cattle but has low nutritional quality. Therefore, this corn waste is fermented to improve its nutritional quality. This study aimed to analyze the effect of straw and corncob fermentation on nutrient content and characteristics of rumen fluid in vitro. This experiment consisted of three (3) experimental stages. Experiment Phase 1: Manufacture of a multifunctional grinding machine. This experiment uses a qualitative method through a description of the tools made. Experiment Phase 2: Processing straw and corncobs with the EM4 fermentation method. This experiment used a completely randomized design with six treatments, namely control (elephant grass and grinting grass), corn straw, fermented corn straw, corncob, and fermented corncob with five replications. The variables measured were nutrient content (dry matter, organic matter, ash, crude protein, crude fat, crude fiber, and extracts without nitrogen. Experiment Phase 3: Test the nutritional quality of fermented corn straw and cobs with the In Vitro method. This experiment used a randomized block design with six treatments, namely control (elephant grass and grinting grass), corn straw, fermented corn straw, corncob, and fermented corncob with four replications. The variables measured were the characteristics of the rumen fluid (pH, VFA, and NH3). The results of the Phase 1 experiment show that the feed grinding machine has specifications adapted to its function. Stage 2 showed that the treatment significantly affected the nutrient content. Stage 3 showed that different treatments had a significant effect on NH3 and no significant effect on pH and VFA. Based on the results of experiments that have been carried out, corncob fermentation can improve its nutritional content.